Emodin up‐regulates glucose metabolism, decreases lipolysis, and attenuates inflammation in vitro大黄素在体内上调糖代谢、减少脂解和抑制炎症反应. (4th September 2014) - Zhang, Xiaoyan; Zhang, Rong; Lv, Pengfei; Yang, Jian; Deng, Yujie; Xu, Jun; Zhu, Rongfeng; Zhang, Di; Yang, Ying
Abstract: Background: Emodin, the major bioactive component of Rheum palmatum, has many different activities, including antitumor, anti‐inflammatory, and antidiabetes effects. Recently, emodin was reported to regulate energy metabolism. In the present study, we further explored the effects of emodin on glucose and lipid metabolism. Methods: Differentiated C2C12 myotubes and 3T3‐L1 adipocytes were treated with or without different concentrations of emodin (6.25, 12.5, 25 or 50 μmol/L) for different time (1 h, 3 h, 12 h, 24 h or 48 h). Glucose metabolism, oxygen consumption, lactic acid levels, glycerol levels, and inflammation pathways were then evaluated. Cells were collected for quantitative polymerase chain reaction (PCR) and western blot analysis. Results: Emodin upregulated glucose uptake and consumption in both C2C12 myotubes and 3T3‐L1 adipocytes, with glycolysis increased. Furthermore, emodin inhibited lipolysis under basal conditions (as well as in the presence of 10 ng/ml tumor necrosis factor (TNF‐)‐α in 3T3‐L1 adipocytes) and significantly decreased phosphorylated perilipin. Moreover, emodin inhibited the nuclear factor‐κB and extracellular signal‐regulated kinase pathways in C2C12 myotubes and 3T3‐L1 adipocytes. Conclusions: Emodin upregulates glucose metabolism, decreases lipolysis, and inhibits inflammation in C2C12 myotubes and 3T3‐L1 adipocytes.